Otomatisasi Pengukuran Tinggi Badan di Puskesmas Bane Pematangsiantar Menggunakan Sensor Ultrasonic Berbasis Arduino Uno - Hutasoit, Fictor Marulitua; Sumarno, Sumarno; Anggraini, Fitri; Gunawan, Indra; Kirana, Ika Okta (Building of Informatics, Technology and Science (BITS), 2019)
Every health test certainly has a height measurement, so it can be measured how tall a person is, starting from the sole of the foot to the head, As in the Puskesmas Bane Pematangsiantar, as for the height measuring device used is still manual, using the meter and the measurement process at do by someone to measure the height of someone who wants to know his height so that the measurement results require more time when the number of people measured exceeds 20 people in other words the manual height gauge is less effective when used during the recruitment period of new employees begins. With these constraints the authors make a tool that can measure height automatically by utilizing the Ultrasonic sensor as a measuring tool and the Arduino Uno microcontroller as a control center by displaying the measurement results on a 16x2 LCD screen. In this result it is expected to replace the manual height measurement tool so that it helps the worker's activities in carrying out his noble duty to provide health services to the general public.